In ovo and dietary administration of oligosaccharides extracted from palm kernel cake influence general health of pre- and neonatal broiler chicks - Jahromi, Mohammad Faseleh; Shokryazdan, Parisa; Idrus, Zulkifli; Ebrahimi, Rohollah; Liang, Juan Boo (Public Library of Science, 2017)
Palm kernel cake (PKC) is the main byproduct from the palm oil industry in several tropical countries that contains considerable amounts of oligosaccharide. We earlier demonstrated beneficial prebiotic effects of oligosaccharides extract of PKC (OligoPKC) in starter and finisher broiler birds. This study was envisaged to elucidate the effects of in ovo and/or oral administration of the OligoPKC on prenatal and post-hatched broiler chicks. A total of 140 broiler (Cobb500) eggs were randomly divided into two groups (n = 70 each), and on day 12 of incubation, eggs in one group received in ovo injection of 0.1 mL (containing 20 mg) of OligoPKC, while those in the other group received 0.1 mL of saline (placebo) solution. Of these in ovo placebo or OligoPKC injected eggs, after hatching, six chicks from each group were sampled for day-one analysis, while 48 chicks from each group were randomly allocated to two dietary regimes involving either no feeding or feeding of OligoPKC through basal diet for a 14 days experiment forming the experimental groups as: (i) saline-injected (Control, C), (ii) OligoPKC-injected (PREBovo), (iii) saline-injected, but fed 1% OligoPKC (PREBd), and (iv) OligoPKC-injected and also 1% OligoPKC (PREBovo+d). In ovo injection of prebiotic OligoPKC had no effect on body weight and serum immunoglobulins concentrations of day old chicks, except for IgG, which was increased significantly (P<0.05). Body weight and feed conversion ratio of 14 days old chicks were neither affected by in ovo injection nor feeding of OligoPKC. However, populations of cecal total bacteria and major beneficial bacteria of the chicks were markedly enhanced by feeding of OligoPKC (PREBd and PREBovo+d > C and PREBovo), but lesser influenced by in ovo OligoPKC injection. Irrespective of its prior in ovo exposure, chicks fed OligoPKC diets had lower population of pathogenic bacteria. Overall serum immunoglobulin status of birds was improved by feeding of OligoPKC but in ovo OligoPKC injection had minor effect on that. In most cases, in ovo OligoPKC injection and feeding of OligoPKC reduced the expression of nutrient transporters in the intestine and improved antioxidant capacity of liver and serum. It is concluded that in ovo injection of OligoPKC increased IgG production and antioxidant capacity in serum and liver of prenatal chicks and had limited carrying-over effects on the post-hatched chicks comparing to the supplementary feeding of OligoPKC.